Legalização da produção madeireira na Amazônia brasileira : análise do manejo florestal comunitário e familiar (MFCF) em uma perspectiva de campo de ação estratégica (CAE) - Andrade, Roberta Amaral de (2017)
Community forest management (CFM), the planned and rational use of forest resources by traditional communities and family farmers, is regarded as one of the strategies to tackle deforestation in the Amazon region. Even with challenges, community associations in the region seek to approve "Sustainable Forest Management Plans" (SFMP), a document required in the first stage of CFM. Assuming that the process of obtaining the SFMP occurs in a "strategic action field" (SAF) (FLIGSTEIN; McADAM, 2011), this work performed two study cases (YIN, 2001) from processes conducted by community associations in the municipality of Lábrea in the State of Amazonas. A strategic action field (SAF) is a “socially constructed arena in which actors with varying resources endowments vie for advantages to achieve their objectives” (FLIGSTEIN, McADAM, 2011). Through the "theoretical lens" of the SAF approach, we sought to understand the elements that influenced the contrasting results obtained in the action: a successful one, with the approval of a SFMP; and an unsuccessful one. Our main objective was to analyze and compare these two processes and, specifically, we proposed to: (a) analyze the influence of other fields and the State; (b) identify incumbent and challengers actors; (c) identify resources and social skill. The case studies had an exploratory and longitudinal orientation. Data were collected through participatory observation; document analysis, and semi-structured interviews, the latter being the main data source. Twenty six people among governmental, nongovernmental and actors from the associations aforementioned were interviewed between 2015 and 2017. The theoretical approach of SAF was used as a guideline for data analysis. We argue that the field under analysis is the subfield of timber production in Lábrea, part of an economic field in transformation, and influenced by an emerging environmental field. Thus, we understand that the processes were influenced by three main elements: the presence of internal governance structures; socially skilled actors; and networks. We understand that the situation of the field and the presence of governance structures enabled the action of socially skilled actors in the successful case; and the absence of governance structures in the unsuccessful one left the process vulnerable to the performance of socially skilled actors in the opposite direction of timber production legalization. We suggest the analysis of the genesis of CFM and a network study as a complementary analysis.